Kajian Arsitektur Neo Vernakular pada Museum Negeri di Kota Bengkulu - Ryu Vitru; Ami Arfianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Currently, the development of knowledge and technology is advancing rapidly, resulting in civilizations and historical legacies being less regarded and appearing outdated. A permanent establishment that engages in the collection, conservation, and research of tangible objects for the purposes of study and tourism is called a museum. One of the famous museums in Bengkulu is the Bengkulu State Museum, which falls under the category of a historical museum. Historical museums typically reflect the culture of the region, which can be observed through the details, forms, and architectural styles present in the Bengkulu State Museum. These details, forms, and styles are studied using a neo-vernacular architectural approach, which adopts elements and principles from traditional vernacular styles but with contemporary interpretations. The findings and discussions from this study can be adapted and applied to other cultural buildings in the city of Bengkulu, thereby creating a harmonious unity among cultural structures. Qualitative data is used in this research, gathered through methods such as observation, interviews, and literature studies.